Intestinal Microbiome Shifts, Dysbiosis, Inflammation, and Non-alcoholic Fatty Liver Disease - Saltzman, Emma T.; Palacios, Talia; Thomsen, Michael; Vitetta, Luis (Frontiers in Microbiology, 2018)
Adverse fluctuations in the distribution of the intestinal microbiome cohort has been correlated with the onset of intra- and extra-intestinal inflammatory conditions, like the metabolic syndrome (MetS) and non-alcoholic fatty liver disease (NAFLD). The intestinal microbial community of obese compared to lean subjects has been shown to undergo configurational shifts in various genera, including but not limited to increased abundances of Prevotella, Escherichia, Peptoniphilus and Parabacteroides and decreased levels of Bifidobacteria, Roseburia and Eubacteria genera. At the phylum level, decreased Bacteroidetes and increased Firmicutes have been reported. The intestinal microbiota therefore presents an important target for designing novel therapeutic modalities that target extra-intestinal inflammatory disorders, such as NAFLD. This review hypothesises that disruption of the intestinal–mucosal macrophage interface is a key factor in intestinal-liver axis disturbances. Intestinal immune responses implicated in the manifestation, maintenance and progression of NAFLD provide insights into the dialogue between the intestinal microbiome, the epithelia and mucosal immunity. The role of inflammatory activity and immune imbalances in NAFLD pathophysiology that stem from dysbiosis of the intestinal epithelia has recently been implicated as a source of hepatoxic effects. We posit that the hepatotoxic consequences of intestinal dysbiosis are compounded through intestinal microbiota-mediated inflammation of the local mucosa that encourages mucosal immune dysfunction, thus contributing important plausible insight in NAFLD pathogenesis. The administration of probiotics and prebiotics as a cure-all remedy for all chronic diseases is not supported. However, evidence based probiotic/prebiotic formulations may provide a beneficial adjunctive intervention for the amelioration of NAFLD.